1998
DOI: 10.1046/j.1365-2265.1998.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of conventional and dynamic magnetic resonance imaging of the pituitary gland for the diagnosis of Cushing's disease

Abstract: In our hands, dynamic procedures did not improve the usefulness of MRI in Cushing's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 29 publications
1
87
0
1
Order By: Relevance
“…In the use of these agents such as gadolinium, differences in the dynamic release of the contrast agent from the vasculature to the interstitial space was examined to differentiate normal pituitary gland from adenoma. [24][25][26][27] These studies found that factors such as surrounding microvasculature, arterial blood supply, size of adenoma, and tumor type (fibrous versus soft) affected the variability in clinical diagnoses. 26 Although we have yet to perform such rigorous investigation on this newly proposed imaging method, the fact that Mn 2ϩ enters into cells by a means that is directly related to the activity of a cell suggests the potential for improved clinical pituitary tumor assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In the use of these agents such as gadolinium, differences in the dynamic release of the contrast agent from the vasculature to the interstitial space was examined to differentiate normal pituitary gland from adenoma. [24][25][26][27] These studies found that factors such as surrounding microvasculature, arterial blood supply, size of adenoma, and tumor type (fibrous versus soft) affected the variability in clinical diagnoses. 26 Although we have yet to perform such rigorous investigation on this newly proposed imaging method, the fact that Mn 2ϩ enters into cells by a means that is directly related to the activity of a cell suggests the potential for improved clinical pituitary tumor assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our recent unpublished data, both the CRH test and 8 mg DST would achieve a higher specific measure for the diagnosis of Cushing's disease when combined with MRI [15,16], because the test results, along with the presence of a pituitary adenoma offer > 90% speficicity in Cushing's disease. In fact, MRI shows a high specificity to diagnose Cushing's disease [17]. The ability of MRI to detect pituitary ACTH-secreting adenomas in patients with Cushing's disease is, however, limited, because the calculated accuracy for detecting a pituitary source of ACTH is reported to be almost 60% for MRI [18].…”
Section: Bmentioning
confidence: 99%
“…Corticotrophic microadenomas are not detectable on imaging studies in 40% to 50% of patients. 1 Bilateral inferior petrosal sinus sampling (IPSS) with corticotropin-releasing hormone (CRH) stimulation is a diagnostic technique that can aid with both the localization of the tumor to the pituitary gland as well as suggest lateralization within the gland. This procedure can also be used in cases of equivocal endocrine testing but established hypercortisolism or before reoperation.…”
mentioning
confidence: 99%